Analisis Pengendalian Persediaan Bahan Baku dengan Menggunakan Metode Material Requirement Planning Pada Bakpia Wirda di Karanganyar - Febri Widya Puspitasari; Erni Widajanti (Pusat Riset dan Inovasi Nasional, 2024)
The Bakpia Wirda Karanganyar Company is a business that operates in the food sector, especially bakpia products, in the production process it requires a lot of raw materials which must be maintained so that the production process can run smoothly. Inventory of raw materials is the main factor in a company to support the smooth production process, both in large and small companies. The key to the production process being able to run smoothly is by controlling optimal and sufficient raw material supplies. A company needs inventory, without inventory the company will run the risk of not being able to meet consumer needs. The aim of this research is to analyze the efficiency of controlling supplies of raw materials for wheat flour and green beans using the Material Requirement Planning (MRP) method, which consists of the Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ) methods. ). The results of the research show that the total cost of raw material inventory according to the policy of the Bakpia Wirda Karanganyar business owner is IDR 1,735,000.35 greater than the calculation using the MRP method. The total cost of raw material inventory using the Lot For Lot (LFL) method is IDR 348,705.84, EOQ is IDR 309,203.31 and using the POQ method is IDR 348,705.84. From the results of calculating the total cost of raw material inventory, the MRP method can streamline raw material inventory costs, especially the EOQ method.